Expeditious Electrochemical Synthesis of Mesoporous Chalcogenide Flakes: Mesoporous Cu2Se as a Potential High‐Rate Anode for Sodium‐Ion Battery. Issue 34 (29th July 2022) - Nagaura, Tomota; Li, Jinliang; Fernando, Joseph F. S.; Ashok, Aditya; Alowasheeir, Azhar; Nanjundan, Ashok Kumar; Lee, Sukho; Golberg, Dmitri V.; Na, Jongbeom; Yamauchi, Yusuke
Abstract: Nanostructured copper selenide (Cu2 Se) attracts much interest as it shows outstanding performance as thermoelectric, photo‐thermal, and optical material. The mesoporous structure is also a promising morphology to obtain better performance for electrochemical and catalytic applications, thanks to its high surface area. A simple one‐step electrochemical method is proposed for mesoporous chalcogenides synthesis. The synthesized Cu2 Se material has two types of mesopores (9 and 18 nm in diameter), which are uniformly distributed inside the flakes. These materials are also implemented for sodium (Na) ion battery (NIB) anode as a proof of concept. The electrode employing the mesoporous Cu2 Se exhibits superior and more stable specific capacity as a NIB anode compared to the non‐porous samples. The electrode also exhibits excellent rate tolerance at each current density, from 100 to 1000 mA g −1 . It is suggested that the mesoporous structure is advantageous for the insertion of Na ions inside the flakes. Electrochemical analysis indicates that the mesoporous electrode possesses more prominent diffusion‐controlled kinetics during the sodiation–desodiation process, which contributes to the improvement of Na‐ion storage performance. Abstract : The proposed synthesis method enables the fabrication of mesoporous Cu2 Se flakes with a huge electrochemically active surface area. Uniformly sized mesopores are homogeneously distributed within the flakes. The mesoporous electrode shows high specific capacity (of more than 300 mAh g −1 ), stable cycling performance, and diffusion‐controlled electrochemical behavior.